Twenty thousand leagues under the sea - Verne, Jules, 1828-1905 (Penguin classics, 2016)
"[T]hree men embark on an epic journey under the sea with the mysterious Captain Nemo aboard his submarine the Nautilus. Over the course of their fantastical voyage, they encounter the lost city of Atlantis, the South Pole and the corals of the Red Sea, and must battle countless adversaries both human and monstrous." --